1997
DOI: 10.1037/1040-3590.9.4.429
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of psychopathy in a population of incarcerated adolescent offenders.

Abstract: The reliability, validity, and factor structure of a modified version of the Psychopathy Checklist-Revised (PCL-R) for adolescents was investigated, completed using file information only, in a sample of incarcerated Black and White male adolescents. Interrater reliability and internal consistency were high, and confirmatory factor analyses and coefficients of congruence showed that the factor structure in this sample resembled the 2-factor solution found in adults. No significant racial differences were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
247
8
18

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(302 citation statements)
references
References 36 publications
29
247
8
18
Order By: Relevance
“…Corrado et al, 2004;Forth et al, 2003;Kosson et al, 2002), and are within the same range as mean scores typically seen in samples of incarcerated youth in the U.S. (i.e. 24; Brandt et al, 1997;Forth et al, 2003). For the 13-item, three-factor model, mean total scores ranged from 2 to 25 (M ¼ 14.12, SD ¼ 4.73).…”
Section: Psychopathic Characteristicssupporting
confidence: 58%
See 1 more Smart Citation
“…Corrado et al, 2004;Forth et al, 2003;Kosson et al, 2002), and are within the same range as mean scores typically seen in samples of incarcerated youth in the U.S. (i.e. 24; Brandt et al, 1997;Forth et al, 2003). For the 13-item, three-factor model, mean total scores ranged from 2 to 25 (M ¼ 14.12, SD ¼ 4.73).…”
Section: Psychopathic Characteristicssupporting
confidence: 58%
“…Psychometric properties of the PCL:YV are similar to the PCL-R and include adequate levels of internal consistency and item homogeneity in samples of adolescent males (alpha range ¼ 0.75-0.89; Brandt, Kennedy, Patrick, & Curtin, 1997;Forth, Hart, & Hare, 1990), as well as good to excellent levels of inter-rater reliability (0.81-0.98; Hume, Kennedy, Patrick, & Partyka, 1996;Toupin et al, 1996). Using intra-class correlation coefficients for a two-way random effects model for absolute groups, the ICC 1 was satisfactory for PCL:YV total score based on file-only training cases (0.87; n ¼ 5).…”
Section: Methodsmentioning
confidence: 97%
“…Each of the 20 items was scored on a threepoint scale (0 ¼ item doesn't apply, 1 ¼ item applies somewhat, 2 ¼ item definitely applies). Reliability studies have demonstrated acceptable levels of internal consistency and inter-rater agreement (e.g., r ¼ 0.81 to r ¼ 0.93; see, e.g., Brandt, Wallace, Patrick, & Curtin, 1997;Forth, 1995;Vincent et al, 1999). The ICC 1 for PCL-YV total scores in the current study was 0.89 (C.I.…”
Section: Pcl-yvmentioning
confidence: 99%
“…Ces prévalences augmentent même lorsque ces adolescents sont pris en charge à la suite du délit sexuel [6]. De même, s'il semble établi que l'abus sexuel peut conduire à des problèmes de comportement sexuel chez les enfants, son rôle étiologique dans la délinquance sexuelle juvénile demeure imprécis [12].…”
Section: Introductionunclassified